(3GdCZdGd hGdSdGSd aj eLfhf CSeg YGbds - (3MSf Hf Ydj bhjOQ GdNdjdj,J (B1262 (3g` s
(3ChdgG (B:s
(3jbhd GdYHO GdPj Ndbg aj Gddg MSf, GdedbH HbhjOQ, GdeSei HMSf(B: (3bO MVQ Edqi HYV GdCMHGH, hCdbi Edi gPG GdcJGH, hCdJeS efj Cf CfhH Yfg aj QO GdLhGH, aEPG gh ef UGMH dg CSeg YGbd s
(3BNQgG (B:s
(3aEPG fXQ GdEfSGf dYdeg aQH Yde ChhQK UGMHg jhe GdbjGeI MSQI, hEf aj VdGd EHdjS eY Ydeg dYHQI QRbfG Gddg MSf GdNGJeI EPG GdYeQ EfJgi, hLYdfG eef EPG oCeQ EFJeQ hEPG fgi GfJgi s
(3gfGc Tc aj Cf GdeNWhW ocJH HNW eDdags
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B206 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B3 - (3U (B258s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B2 - (3U (B49 s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3COH JjehQ (B618) s
Keywords: (3GdCOHs